Consequences of Play: A Systematic Review of the Effects of Online Gaming - Sublette, V.; Mullan, Barbara (Springer, 2012)
Massively Multiplayer Online Games (MMOGs) have received considerable attention in news headlines describing gamers who have died while engaging in excessive play. However, more common physical and psychosocial effects attributed to online video gaming are social isolation, increased aggression, and negative academic and occupational consequences. In consideration of the bias in reporting negative consequences of video gaming, a systematic review was conducted to evaluate the evidence of the effects of MMOGs on those who play them. In the sixteen studies that met the inclusion criteria, analysis revealed that only those players who were classified as “addicted” or engaged in “problematic game play” experienced significant negative consequences, with many gamers finding positive aspects to video gaming such as enjoyment, feelings of achievement, friendship, and a sense of community. However, significant limitations in the studies point to the need for further research so that appropriate treatments and interventions can be developed for problematic game play.